Quantification of Antioxidant Ability Against Lipid Peroxidation with an 'Area Under Curve' Approach - Bakir, Temelkan; Sonmezoglu, Inci; Apak, Resat (WILEY, 2017)
When oxygen is passed through a linoleic acid (LA) emulsion containing copper(II), primary (hydroperoxides) and secondary oxidation products (aldehydes and ketones) are formed, monitored by ferric thiocyanate (Fe(III)-SCN) and thiobarbituric acid reactive substances (TBARS) colorimetry, respectively. As total antioxidant capacity (TAC) against lipid peroxidation was not quantified before, both methods were adapted to an 'area under curve (AUC)' approach. LA peroxidation followed pseudo-first order kinetics in aerated emulsions. Absorbance changes as a function of incubation time exhibited sigmoidal curves, enabling the calculation of 'area under curve' (AUC) and net AUC = AUC(blank)-AUC(sample), standard calibration curve as net AUC versus concentration, and trolox-equivalent antioxidant capacity of the tested compounds. Garlic extract showed an antioxidative effect on hydroperoxide formation, but a prooxidative effect on TBARS. Although inhibition of lipid peroxidation was described qualitatively before, it was not evaluated quantitatively, e.g., the trolox-equivalent antioxidant capacities (TEAC values) of antioxidants with respect to their inhibitive effect against lipid peroxidation were not calculated and compared. Additionally, real-time monitoring of lipid oxidation products requires highly sophisticated but costly instrumental techniques, but no single oxidation product is a direct measure of lipid oxidation or its antioxidative prevention. The AUC approach is the first quantitative method measuring antioxidant protection against lipid oxidation, with a slightly different order of antioxidative effectiveness from reductive assays because of interfacial effects.
Keywords: Lipid peroxidation; Antioxidant capacity; Colorimetry; Ferric thiocyanate; Thiobarbituric acid-reactive substances (TBARS); Area under curve (AUC); LINOLEIC-ACID; CAPACITY; MALONDIALDEHYDE; HYDROPEROXIDES; CHEMISTRY; OXIDATION; EXTRACTS; Food Science & Technology